Soil mercury accumulation and transference to different crop grains. Issue 5 (3rd July 2016) - Hang, Xiaoshuai; Gan, Fangqun; Wang, Jianguo; Chen, Xiaoqin; Chen, Yudong; Wang, Huoyan; Zhou, Jianmin; Du, Changwen
ABSTRACT: Mercury contamination in agro-ecosystems is one of the most important environmental issues. Farmland soil mercury accumulation and transference to crops in Changshu City, eastern China, were investigated to identify mercury migration capacity from soil to crops. The mean content of mercury for soil samples slightly increased year after year. The mercury accumulation capacity of rice grown (bioaccumulation factor (BAF) 0.028) in submerged soils under reductive conditions was stronger than that of wheat (BAF 0.0073) in dried soils under oxidative conditions. There were clear relationships between soil mercury with organic matter (OM), cation exchange capacity (CEC), and CaCO3 of soil samples, while apparent negative relationships between Hg in rice grain with OM, CEC, and CaCO3 of soil existed. No clear association for Hg between crops and soil was found, indicating that mercury in crop grains is mostly affected by other factors besides soil mercury. Also, soil properties and farming patterns affected mercury transference from soil to crop grains and mercury enrichment capacity in crop grains. The results suggested that appropriate selection of crop species and water management are two major possible ways to reduce total mercury accumulation in crop grains grown in mercury-contaminated regions.